Validation of Soccer Shooting Skills Test in Junior High School Students - Widodo, Achmad; Wismanadi, Himawan; Wahyudi, Heri; Fikri, Muhammad Dzul; Firmansyah, Awang (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2022)
The purpose of the study was to develop a test instrument of shooting skill that is valid and reliable on junior high school soccer students (13-15 years) as many as 33 subjects. The approach of this type of research is the development, the sampling using purposive sampling method that has the criteria of Junior High School students aged 13-15 years (male) who are hobbyists and proficient in soccer. The results of the test validity test showed that the level of validity of the instrument shooting skills test on right and left foot 0.89 with perfect category, and has a reliability value of R = 0.78 (medium), left r = 0.83 (high). The conclusion of this study is that the instrument tests of shooting skill with the closest distance to the goal of 15m using the right and left limbs have a level of validity that meets the standards. Thus the instrument tests of shooting skill can be used to measure and assess the technical skills of playing kicking the ball into the football goal at the junior high school level (13-15 years).